Minimizing flood damage and augmenting dry season water availability: prospects for floodwater harvesting and underground storage in Sri Lanka - Eriyagama, Nishadi; Muthuwatta, Lal P.; Thilakarathne, Madusanka (2014)
Flood water harvesting and underground storage is a concept that has received significant attention in many regions of the world. Its intention is to capture floodwater from currently flooded areas and to store it for later use, in order to both, reduce damage caused by floods, as well as to satisfy demands for water during drier periods. This paper presents a preliminary analysis of the prospects for its realization in Sri Lanka. A coarse scale suitability index is constructed and mapped at district level in order to identify the districts having higher prospects for its implementation. Preliminary results indicate three main clusters of highly suitable districts, subject to favourable geological conditions. Cluster 1 consists of Ampara and Batticalao, Cluster 2 of Kurunegala, Anuradhapura and Mannar, and Cluster 3 of Ratnapura. The potential for groundwater recharge of the highly suitable clusters need special investigation prior to arriving at concrete conclusions. If successfully implemented, this concept may prove a valuable intervention for adapting to current and future floods and droughts.